Involvement of serotonergic pathways in gastric dysmotility induced by fat burning nutritional supplements in mice - Luciano N. de Sousa; Débora S. Paraguassú Sant'ana; Rildo G. Siqueira dos Santos; Anita Eugênia A. dos Santos Ribeiro; Camila F. da Costa; Ana Paula de Oliveira; Jackson Roberto G. da Silva Almeida; Davi M. Jucá; Moisés Tolentino; Armênio A. dos Santos; Raimundo C. Palheta Junior (Elsevier, 2021)
Fat burners are a category of nutritional supplements that are claimed to increase the metabolism and promote greater energy expenditure, leading to weight loss. However, little is known about the side effects on gastrointestinal motility. In this study, we evaluated the effect of ingestion with a fat burner named Thermbuterol® (THERM) on the gastric motility and food behavior of mice. THERM compounds were identified using nuclear magnetic resonance (NMR). Mice received variable doses of THERM (10, 50, 100 or 300 ​mg/kg, p.o.) or NaCl 0.15 ​M (control). Gastric emptying (GE) was assessed using the phenol red technique. Another set of mice was pretreated with intraperitoneal administration of hexamethonium (HEXA, 10 ​mg/kg), prazosin (PRAZ, 0.25 ​mg/kg), propranolol (PROP, 2 ​mg/kg), parachlorophenylalanine (PCPA, 300 ​mg/kg) or ondansetron (ONDA, 50 ​μg/kg) 30 ​min before THERM treatment for evaluation of GE. We assessed the gastrointestinal responsiveness in vitro as well as THERM's effects on food behavior. Caffeine was the major compound of THERM, identified by NMR. THERM 100 and 300 ​mg/kg decreased GE compared to the respective controls. Pretreatment with PRAZ or PROP did not prevent gastric dysmotility induced by THERM 100 ​mg/kg. However, the pretreatment with HEXA, ONDA or PCPA prevented GE delay induced by THERM. In vitro, THERM relaxed contractions in strips of longitudinal gastric fundus and duodenum. THERM also increased food intake, which was prevented by PCPA and ONDA treatments. THERM decreased GE of a liquid and increased food intake in mice, a phenomenon mediated by the autonomic nicotinic receptors and serotoninergic receptor.